(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
The article discusses the problems of professional personal qualities. Also, the characteristics of the psychological personalities of different professionals. The article describes the educational impact of the officer on the personnel units and the important features of the military educator